The rho kinase inhibitor Y-27632 improves motor performance in male SOD1G93A mice - Günther, René; Saal, Kim-Ann; Suhr, Martin; Scheer, David; Koch, Jan Christoph; Bähr, Mathias; Lingor, Paul; Tönges, Lars (Frontiers in Neuroscience, 2014)
Disease progression in amyotrophic lateral sclerosis (ALS) is characterized by degeneration of motoneurons and their axons which results in a progressive muscle weakness and ultimately death from respiratory failure. The only approved drug, riluzole, lacks clinical efficacy so that more potent treatment options are needed. We have identified rho kinase (ROCK) as a target, which can be manipulated to beneficially influence disease progression in models of ALS. Here, we examined the therapeutic potential of the ROCK inhibitor Y-27632 in both an in vitro and in an in vivo paradigm of motoneuron disease. Application of Y-27632 to primary motoneurons in vitro increased survival and promoted neurite outgrowth. In vivo, SOD1G93A mice were orally treated with 2 or 30 mg/kg body weight of Y-27632. The 2 mg/kg group did not benefit from Y-27632 treatment, whereas treatment with 30 mg/kg resulted in improved motor function in male mice. Female mice showed only limited improvement and overall survival was not modified in both 2 and 30 mg/kg Y-27632 groups. In conclusion, we provide evidence that inhibition of ROCK by Y-27632 is neuroprotective in vitro but has limited beneficial effects in vivo being restricted to male mice. Therefore, the evaluation of ROCK inhibitors in preclinical models of ALS should always take gender differences into account.